Laparoscopic repair of a Morgagni diaphragmatic hernia in a child, using a trans-sternal technique - Shah Amar; Jawaheer Girish (Journal of Indian Association of Pediatric Surgeons, 2005)
Laparoscopic repair of Morgagni hernia has been described in adults and children. In the published reports, the crux of the repair consists of suturing the posterior part of the diaphragmatic defect to the undersurface of the sternum or the posterior rectus sheath. The tissue on the undersurface of the sternum is variable is in its nature and may be inadequate for suturing, hence compromising the strength of the repair. A technique that circumvents this problem and offers a strong anatomical repair is described. A Morgagni hernia was diagnosed in a 2-year-old girl with trisomy 21, who presented with recurrent chest infections. She underwent laparoscopic repair of the hernia using three ports. The tissue on the undersurface of the sternum was inadequate for a conventional repair. The procedure was modified as follows: a small transverse incision was made over the lower end of the sternum. Three nonabsorbable mattress sutures were inserted through the sternum, the anterior edge of the diaphragmatic defect, and back through the sternum and tied with extracorporeal knots. The child was discharged home on the second postoperative day. At 6-month follow up, the child was asymptomatic, and had been infection free. A chest radiograph was normal. This is a simple, novel, noninvasive method, which offers a secure anatomical repair and it is not dependent on the adequacy of the tissue on the undersurface of the sternum.